Identifying Purine Intake Among People with Gout and Its Relationship with Uric Acid Level: A Cross-Sectional Study - Yusron Amin; Haswita Haswita; Sephya Nola Tiarasari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Gout was still one of the chronic disease trends suffered by the community which was characterised by elevated uric acid levels. This condition is closely related to lifestyle, namely the consumption of purine-rich foods. However, there were not studies that discovered the relationship between purine-rich food intake with elevated uric acid levels. This study aims to analyse the relationship between purine-rich food intake with elevated uric acid levels. This study used a correlational design with a cross-sectional approach. The population was the community in village